Three new species of Stelis (Orchidaceae; Pleurothallidinae) from Mexico - Solano Gomez, Rodolfo (Phytotaxa, 2014)
Three new species in the genus Stelis (Orchidaceae) are here described and illustrated for the first time: two have been previously mentioned and are published formally here. For each taxon, information is provided about its distribution, habitat, phenology, traits that distinguish it from similar species, and conservation status. A line drawing, photo, and map for the known localities of the three species are provided.